What a wonderful world - Weiss, George (George David); Bryan, Ashley; Thiele, Bob. (New York : Atheneum Books for Young Readers, 1995)
Ashley Bryan's artwork depicts Louis Armstrong and children of many backgrounds performing a puppet show that brings to life the song Armstrong made famous.
"A Jean Karl book."
Book Links (A.L.A.)
Elem. School Library Collection
School Library Journal
2.3
K-3
Keywords: Children's poetry, American; American poetry; American poetry